Improvement of the ultrasonographic image of the equine digestive organs through the use of different contrast solutions (Veterinary Science, 2017)
The overall purpose of this study was to make a clinical examination and ultrasonographic protocol of the integrity of the gastrocolic response and the anatomophysiology of the stomach, small intestine, ileocecal valve, cecum and colon of horses. The gastrocolic response was caused by the rapid provision of enteral fluids via nasogastric tube. Emptying of the stomach was recorded by ultrasonography. The bowel function was assessed by comparing physical examination with ultrasound image simultaneously. Technique was applied transcutaneous to evaluate the transit from the stomach into the intestine and the influence of rapid gastric filling has on colonic motility. The evaluation of the images produced during fasting, ingestion of solid foods and fluids with different formulation was made for the purpose of weighing the degree of improvement of the ultrasound image, which allowed us to obtain accurate data on digestive function.
Keywords: Horses; Gastrocolic response; Clinical examination; Ultrasound